Retrospective analysis of HSG in primary infertility - Mishra, R K; Dave, P K; Jain, M; Bhardwaj, Malini; Jain, S (International Journal of Medical Research and Review, 2017)
Introduction: Hysterosalpingography used to be a common Radiological Investigation since long time for the investigation of infertility. In the current era of imaging HSG remains to be a choice of investigation for infertility cases. It provides anatomical depiction of uterus and fallopian tubes by introduction of contrast agent. Objective: Objective of this study is to analyze the common pathological conditions detected on HSG in cases of primary infertility. Methodology: 140 cases of HSG were reviewed retrospectively in cases of primary infertility. Study covered age ranging from 20 yrs to 42 yrs. The largest number of patients who reported were between the age of 26 – 30 years –47.14 %. Maximum patients were in the marital duration of 2-5 yrs -65%, followed by 6-10 Yrs -24% and remaining 16 % above the duration of more than 10 yrs. Routine use of contraceptives by both partners were excluded in this study. Infertility caused by the male factor was al1so excluded. Standard protocol for HSG was followed with use of water soluble contrast. Results: Analysis of 140 cases show common cause of infertility as congenital uterine anomalies - 6.42 %, various levels of tubal blocks–17.2%, Uterine SOL/ Fibroid– 4.28% and pelvic adhesions- 6.42%. Conclusion: Hysterosalpingography still remains the choice of investigation in cases of primary infertility. Most of the cases with primary infertility had a normal HSG, followed by various uterine congenital anomalies and fallopian tube obstruction with or with hydrosalpinx.HSG is repeatable, cost effective, safe and less time-consuming procedure except for the fact that it involves small X-ray exposure to patient.